Global Patterns of Prostate Cancer Incidence, Aggressiveness, and Mortality in Men of African Descent - Timothy R. Rebbeck; Susan S. Devesa; Bao-Li Chang; Clareann H. Bunker; Iona Cheng; Kathleen Cooney; Rosalind Eeles; Pedro Fernandez; Veda N. Giri; Serigne M. Gueye; Christopher A. Haiman; Brian E. Henderson; et al. (Prostate Cancer)
Prostate cancer (CaP) is the leading cancer among men of African descent in the USA, Caribbean, and Sub-Saharan Africa (SSA). The estimated number of CaP deaths in SSA during 2008 was more than five times that among African Americans and is expected to double in Africa by 2030. We summarize publicly available CaP data and collected data from the men of African descent and Carcinoma of the Prostate (MADCaP) Consortium and the African Caribbean Cancer Consortium (AC3) to evaluate CaP incidence and mortality in men of African descent worldwide. CaP incidence and mortality are highest in men of African descent in the USA and the Caribbean. Tumor stage and grade were highest in SSA. We report a higher proportion of T1 stage prostate tumors in countries with greater percent gross domestic product spent on health care and physicians per 100,000 persons. We also observed that regions with a higher proportion of advanced tumors reported lower mortality rates. This finding suggests that CaP is underdiagnosed and/or underreported in SSA men. Nonetheless, CaP incidence and mortality represent a significant public health problem in men of African descent around the world.